(untitled) (Jurnal Agregasi : Aksi Reformasi Government dalam Demokrasi, 2023)
The commitment of the Sumedang Regency government in realizing governance and development based on local culture is manifested through the policy of Sumedang Puseur Budaya Sunda (SPBS)/Sumedang Regency as Center of Sundanese Culture. But in practice, the SPBS policy has not been able to create governance and development based on Sundanese cultural values. On this basis, this article aims to examine the inhibiting factors of SPBS policy implementation. The research methods carried out through descriptive research methods with a qualitative approach. The results revealed that the inhibiting factors of SPBS policy implementation consisted of 2 (two) main factors, namely: First, substantially the values ​​of Sundanese culture can only be realized philosophically, while the values ​​of Sundanese culture are both managerial and operations have not been able to be constructed practically in both governance and development. Second, SPBS policy which requires the involvement of all stakeholders in practice is mostly carried out by the Sumedang Regency government. On this basis, the implementation of SPBS policy in the future must be supported by clear and detailed policy instruments containing the subsistence of operational values of Sundanese culture, as well as the active role of stakeholders to jointly succeed the SPBS policy.